Pengaruh Brand Ambassador dan Flash Sale Terhadap Impulse Buying Consumer di Marketplace Shopee Pada Generasi Z - Layyina Galuh Purnama; Yayan Hendayana; Ari Sulistyowati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study aims to examine the effect of Brand Ambassadors and Flash Sale on Impulse Buying in the Shopee marketplace. The sampling technique in this study is Generation Z who uses the Shopee application. The instrument for collecting data in this study was a questionnaire with 120 respondents. In this study using multiple linear regression analysis using SPSS 26 software. The results of this study indicate that the Brand Ambassador (X1) and Flash Sale (X2) variables have a significant positive effect on Impulse Buying in the Shopee marketplace. In the coefficient of determination, the brand ambassador and flash sale variables have an effect of 36.4% on impulse buying consumers and the remaining 63.6% is influenced by other variables outside this study.